Overview of national construction market in the Republic of Croatia - Mariela Sjekavica Klepo; Mate Damić; Goran Milaković; Siniša Radaković; Petar Peroš (Građevinar)
A trend of strong construction works prices’ growth has been noticed from 2018. This is particularly challenging from a strategic perspective for the Republic of Croatia in the context of complex infrastructure projects co-financed by the European Union, given the rules for implementing EU co-financed projects - primarily the implementation period, eligibility of costs, and achievement of performance indicators. Increasing costs on these projects generally requires an increase in the amount of national co-financing, with implementation difficulties arising from the necessary approval procedures for such increases. To analyse this trend in detail and elaborate its possible antecedents, an overview of national construction market up to 2020 is given in this paper. Results of construction industry indicators’ analysis are shown, as well as their synthesis in accordance to the relationship between supply and demand. By exploring this market trend from technical and economical side, an unique overview for understanding it from perspective of historical trends is given; and possible factors that may contribute to a significant increase in the average offered prices of construction work in the Republic of Croatia are listed.